Antiepileptic Drug Teratogenicity and De Novo Genetic Variation Load. Issue 6 (15th April 2020) - Perucca, Piero; Anderson, Alison; Jazayeri, Dana; Hitchcock, Alison; Graham, Janet; Todaro, Marian; Tomson, Torbjörn; Battino, Dina; Perucca, Emilio; Ferri, Meritxell Martinez; Rochtus, Anne; Lagae, Lieven; et al.
Abstract : Objective: The mechanisms by which antiepileptic drugs (AEDs) cause birth defects (BDs) are unknown. Data suggest that AED‐induced BDs may result from a genome‐wide increase of de novo variants in the embryo, a mechanism that we investigated. Methods: Whole exome sequencing data from child–parent trios were interrogated for de novo single‐nucleotide variants/indels (dnSNVs/indels) and de novo copy number variants (dnCNVs). Generalized linear models were applied to assess de novo variant burdens in children exposed prenatally to AEDs (AED‐exposed children) versus children without BDs not exposed prenatally to AEDs (AED‐unexposed unaffected children), and AED‐exposed children with BDs versus those without BDs, adjusting for confounders. Fisher exact test was used to compare categorical data. Results: Sixty‐seven child–parent trios were included: 10 with AED‐exposed children with BDs, 46 with AED‐exposed unaffected children, and 11 with AED‐unexposed unaffected children. The dnSNV/indel burden did not differ between AED‐exposed children and AED‐unexposed unaffected children (median dnSNV/indel number/child [range] = 3 [0–7] vs 3 [1–5], p = 0.50). Among AED‐exposed children, there were no significant differences between those with BDs and those unaffected. Likely deleterious dnSNVs/indels were detected in 9 of 67 (13%) children, none of whom had BDs. The proportion of cases harboring likely deleterious dnSNVs/indels did not differ significantly between AED‐unexposed and AED‐exposed children. The dnCNV burden was not associated with AED exposure or birth outcome. Interpretation: Our study indicates that prenatal AED exposure does not increase the burden of de novo variants, and that this mechanism is not a major contributor to AED‐induced BDs. These results can be incorporated in routine patient counseling. ANN NEUROL 2020;87:897–906